Gestion De Inventario En La Hacienda Bananera Adrianita - Ocaña Alomoto, Sindy Belén (2019)
Companies have had and have had inventory problems for a long time, which in some cases affected the solvency or liquidity of the products required by the banana plantation in order to dose some of the products such as glyphosate to eradicate the weeds of the banana, covers for the protection of the banana bunch, ribbons of different colors to mark the product, among other products, and in some cases they are not well managed or distributed, and in others there is not the trained personnel for this function as is the management and control of them.